Rapid Systematic Review of Normal Audiometry Results as a Predictor for Benign Paroxysmal Positional Vertigo. (June 2014) - Dorresteijn, Paul M.; Ipenburg, Norbertus A.; Murphy, Kathryn J.; Smit, Michelle; van Vulpen, Jonna K.; Wegner, Inge; Stegeman, Inge; Grolman, Wilko
Objective: To evaluate whether absence of hearing loss on pure-tone audiometry (PTA) is reliable as a diagnostic test for predicting benign paroxysmal positional vertigo (BPPV) in adult patients with vertigo. Data Sources: PubMed, Embase, and the Cochrane Library. Methods: A systematic literature search was conducted on December 10, 2013. Relevant publications were selected based on title, abstract, and full text. Selected articles were assessed for relevance and risk of bias using predetermined criteria. Prevalence and the positive and negative predictive value (PPV and NPV) were extracted. Results: Of 603 retrieved publications, 1 article with high relevance and moderate risk of bias was included. In this study, the prevalence of BPPV was 28%. The PPV of hearing loss assessed by PTA was 31% (95% CI, 17-49) and the NPV was 73% (95% CI, 61-83). The absence of hearing loss on PTA decreased the risk of BPPV by 1%. Conclusion and Recommendation: There is insufficient high-quality evidence regarding the diagnostic value of the absence of hearing loss, assessed by PTA, for predicting BPPV in adult patients with vertigo.